2019
DOI: 10.1080/0886022x.2019.1612429
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology investigation and analysis of patients with hemodialysis in Sichuan province of China

Abstract: Objectives: To investigate the incidence, pathogenesis, as well as mortality rate and causes of end-stage renal disease patients with hemodialysis (ESRD-HD) in Sichuan province of China. Methods: In this retrospective descriptive study, all the data were exported from the Chinese National Renal Data System (CNRDS). The demographic and pathogenic information from 01 January 2011 to 31 December 2016 were statistically analyzed. Results: According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Several possible explanations of this phenomenon are as follows: (a) Obesity and central obesity may play an indirect role in mediating the pathophysiological development [43]. The prevalence of obesity and central obesity were significantly higher in female (32.3% and 74%, respectively) compared with the male (16.9% and 33.1%, respectively) in this study, which was consistent with the finding of Yu’s [44]; (b) the differences in physiological structure (e.g., glomerular structure and muscle mass) and hormone metabolism between men and women may partly explain this phenomenon [42]; (c) data from the Chinese National Renal Data System (CNRDS) showed that there were more male end-stage renal disease patients with hemodialysis (ESRD-HD) patients than female patients (1.5:1, respectively), and the incidence of ESRD-HD patients obtaining HD was higher in males than in the female population [45]. The result suggested that the access to medical care was substantially limited for women, which might partly explain a higher prevalence of CKD in the females.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible explanations of this phenomenon are as follows: (a) Obesity and central obesity may play an indirect role in mediating the pathophysiological development [43]. The prevalence of obesity and central obesity were significantly higher in female (32.3% and 74%, respectively) compared with the male (16.9% and 33.1%, respectively) in this study, which was consistent with the finding of Yu’s [44]; (b) the differences in physiological structure (e.g., glomerular structure and muscle mass) and hormone metabolism between men and women may partly explain this phenomenon [42]; (c) data from the Chinese National Renal Data System (CNRDS) showed that there were more male end-stage renal disease patients with hemodialysis (ESRD-HD) patients than female patients (1.5:1, respectively), and the incidence of ESRD-HD patients obtaining HD was higher in males than in the female population [45]. The result suggested that the access to medical care was substantially limited for women, which might partly explain a higher prevalence of CKD in the females.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is irreversible; when it progresses to stage 5, patients experience kidney failure that requires replacement therapy (e.g., dialysis treatment) to prolong life. However, in 2016, the annual mortality rate of patients with hemodialysis in Sichuan Province, China was 58.39% person-years (5). Effective management including early initiation of dialysis treatment is critical for delaying the progression of CKD (6).…”
Section: Introductionmentioning
confidence: 99%
“…YouTube was selected because it is among the top 2 platforms in terms of user penetration in Western countries [ 9 ]. Although YouTube is readily accessible and is a popular platform for viewing video content in many parts of the world, it is inaccessible in some Asian countries such as China, which has seen a rapid increase in the need for dialysis over the past decade [ 10 ]. Hence, WeChat was selected as an additional broadcast platform.…”
Section: Discussionmentioning
confidence: 99%